A study on how HIV and AIDS-related stigma and discrimination contribute to the spread of HIV among internally displaced populations in Gulu District, Uganda - Anguria, Sam Edison (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.